Chronic cigarette smoke exposure and pneumococcal infection induce oropharyngeal microbiota dysbiosis and contribute to long-lasting lung damage in mice. Issue 12 (9th December 2020) - Hilty, Markus; Wüthrich, Tsering M.; Godel, Aurélie; Adelfio, Roberto; Aebi, Susanne; Burgener, Sabrina S.; Illgen-Wilcke, Brunhilde; Benarafa, Charaf
Abstract : Environmental factors, such as cigarette smoking or lung infections, may influence chronic obstructive pulmonary disease (COPD) progression by modifying the respiratory tract microbiome. However, whether the disease itself induces or maintains dysbiosis remains undefined. In this longitudinal study, we investigated the oropharyngeal microbiota composition and disease progression of mice (in cages of 5–10 mice per cage) before, during and up to 3 months after chronic cigarette smoke exposure or exposure to room air for 6 months. Cigarette smoke exposure induced pulmonary emphysema measurable at the end of exposure for 6 months, as well as 3 months following smoke exposure cessation. Using both classical culture methods and 16S rRNA sequencing, we observed that cigarette smoke exposure altered the relative composition of the oropharyngeal microbiota and reduced its diversity ( P <0.001). More than 60 taxa were substantially reduced after 6 months of smoke exposure ( P <0.001) However, oropharyngeal microbiota disordering was reversed 3 months after smoke exposure cessation and no significant difference was observed compared to age-matched control mice. The effects of lung infection with Streptococcus pneumoniae on established smoke-induced emphysema and on the oropharyngeal microbiota were also evaluated. Inoculation with S. pneumoniae induced lung damage and altered the microbiota composition for a longer time compared to control groups infected but not previously exposed to smoke ( P =0.01). Our data demonstrate effects of cigarette smoke and pneumococcus infection leading to altered microbiota and emphysema development. The reversal of the disordering of the microbiota composition, but not lung damage, following smoke exposure cessation and after clearance of infection suggest that changes in lung structure are not sufficient to sustain a disordered microbiota in mice. Whether changes in the airway microbiota contribute to inducing emphysema requires further investigation.